Lost treasure of the emerald eye - Stilton, Geronimo; Wolf, Matt; Nithael, Mark; Stevens, Kat; Scholastic Inc. (New York : Scholastic, 2004)
The discovery of an old map by his sister Thea leads Geronimo and his family to search for buried treasure on a faraway island.
Translated from the Italian.
4.1.
3-6.
530L
O
Keywords: Mice -- Juvenile fiction; Journalists -- Juvenile fiction; Treasure troves -- Juvenile fiction; Islands -- Juvenile fiction; Mice -- Fiction; Journalists -- Fiction; Buried treasure -- Fiction; Islands -- Fiction; Adventure and adventurers -- Fiction; Humorous stories; Detective and mystery fiction; Action and adventure fiction